Thalidomide Suppresses Angiogenesis Through the Signal Transducer and Activator of Transcription 3/SP4 Signaling Pathway in the Peritoneal Membrane - Zhu, Nan; Wang, Ling; Guo, Huimin; Jia, Jieshuang; Gu, Lijie; Wang, Xuan; Yang, Man; Guan, Haochen; Yuan, Weijie (Frontiers in Physiology, 2021)
Peritoneal angiogenesis is the key pathophysiological factor that limits peritoneal ultrafiltration during peritoneal dialysis (PD) in uraemic patients. Thalidomide has been confirmed to inhibit angiogenesis by inhibiting the secretion of vascular endothelial growth factor (VEGF), but the exact mechanism by which thalidomide inhibits vascular proliferation during PD is still unclear. Here, the objective of the present study was to investigate whether the reduction in VEGF production by human peritoneal mesothelial cells (HPMCs) was controlled by thalidomide. Stimulation of HPMCs with IL-6 in combination with soluble IL-6 receptor (sIL-6R) promoted VEGF expression and secretion, but these effects were attenuated by thalidomide treatment through a transcriptional mechanism that involved STAT3 and SP4. Conditioned medium from HPMCs cultured with thalidomide inhibited angiogenic endothelial tube formation, which could be further blocked by silencing SP4 and promoted by overexpressing SP4. In vivo, induction of peritoneal angiogenesis in sham rats, 5/6 nephrectomy (5/6Nx) rats, 5/6Nx+PD rats and 5/6Nx+PD rats intraperitoneally treated with thalidomide showed that thalidomide was involved in the control of several key endothelial–specific targets, including VEGFR2, VEGFR3, SP1, SP4 and STAT3 expression and new vessel formation, confirming the role of thalidomide and STAT3/SP4 signalling in these processes. Taken together, these findings identify a novel mechanism that links thalidomide, STAT3/SP4 signalling and angiogenesis in the peritoneal membrane.